Organizational change [5th ed.] an action-oriented toolkit - Deszca, Gene; Ingols, Cynthia; Atanassova, Evelina; Cawsey, Tupper F. (2025)
"The world has continued to churn in very challenging ways since the publishing of the fourth edition of this text. Increasing international tensions, wars in the Ukraine, Sudan, and elsewhere, uneven and shifting global patterns of growth in the aftermath of COVID shutdowns, inflationary pressures, rising interest rates, political instability, and increasing income inequality are heightening political instability in many parts of the world. Serious trade disputes are threatening to transform trade patterns and reshaping supply chains. The massive credit crisis of a decade ago was followed by unprecedented worldwide government stimulus spending and low interest rates to promote growth, which, in turn, resulted in escalating public debt, exacerbated in some nations through tax cuts. Public finances were then impacted by COVID, further stressing the capacity of some national governments to respond to future economic difficulties. Wars and civil insurrections in the Ukraine, parts of Africa, the Middle East, and Asia have sent masses of people searching for safety in new places. Simultaneously, deteriorating international relationships involving major powers, fears of future global pandemics, and the staying power of radical Islamist groups such as al-Qaeda and ISIS affiliates, Boko Haram, and Jemaah Islamiyah have shaken all organizations in affected regions-big or small, public or private. Escalating concerns related to global warming and the extreme weather events it triggers, species extinctions, and rising sea levels are stressing those who recognize the need for sustainable action in governments and organizations of all shapes and sizes as they attempt to figure out how to constructively address these escalating threats to life as we know it. Add to these elements the accelerating pace of technological change and the growing concerns about the potential impact of artificial intelligence, and it's easy to see why we, at times, feel overwhelmed by the turbulence, uncertainty, and negative prognosis that seem to define the present"--
Keywords: Organizational change